MENINGKATKAN KEMAMPUAN KOMUNIKASI SOSIAL MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING SISWA KELAS V SDN 005 LANGGINI - Siti Nurdiana; Rizki Ananda; Mufarizuddin; Iis Aprinawati; Putri Hana Pebriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low social communication skills of fifth grade students of SDN 005 Langgini. Therefore, the researcher determines an alternative solution to the problem in the form of implementing learning using the discovery learning model to improve the social communication skills of fifth grade students of SDN 005 Langgini. The type of research applied is (PTK) Classroom Action which is carried out in two cycles of stages in the form of planning stages, implementation stages, observation stages, and reflection stages. The data collection techniques used are observation and documentation techniques. The collected data will then be processed using qualitative and quantitative processing techniques. The results of the study obtained were an increase in students' social communication skills with the implementation of the Discovery Learning learning model for grade V students of SDN 005 Langgini in the subject of Science, the material of Indonesia is rich in culture, increasing especially in the second cycle, as seen from the results of the observation sheets that have been carried out by researchers in each cycle. During cycle I meeting 1, the success rate was only 29.5% and the second meeting was 39.6% which reflects a success rate of only 34.3% and this is included in the less category. While in cycle II meeting 1 the success rate was 53.8% and the second meeting was 81% which reflects a success rate of 76.8% this is included in the good category